2014
DOI: 10.1128/aac.02405-14
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on the Antileishmanial Mechanism of Action of the Arylimidamide DB766: Azole Interactions and Role of CYP5122A1

Abstract: c Arylimidamides (AIAs) are inspired by diamidine antimicrobials but show superior activity against intracellular parasites. The AIA DB766 {2,5-bis[2-(2-i-propoxy)-4-(2-pyridylimino)aminophenyl]furan hydrochloride} displays outstanding potency against intracellular Leishmania parasites and is effective in murine and hamster models of visceral leishmaniasis when given orally, but its mechanism of action is unknown. In this study, through the use of continuous DB766 pressure, we raised Leishmania donovani axenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…In vitro synergy has been described between the squalene synthase inhibitor E5700 and both posaconazole and itraconazole against intracellular L. amazonensis (29). We earlier reported in vitro synergy between DB766 and posaconazole in an intracellular assay using ␤-lactamase-expressing L. donovani parasites (7). However, the results described here, obtained from a high-content assay using wild-type L. donovani parasites, indicates an additive or indifferent interaction between these compounds.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In vitro synergy has been described between the squalene synthase inhibitor E5700 and both posaconazole and itraconazole against intracellular L. amazonensis (29). We earlier reported in vitro synergy between DB766 and posaconazole in an intracellular assay using ␤-lactamase-expressing L. donovani parasites (7). However, the results described here, obtained from a high-content assay using wild-type L. donovani parasites, indicates an additive or indifferent interaction between these compounds.…”
Section: Discussioncontrasting
confidence: 60%
“…Analysis of the interaction between DB766 and posaconazole using fixed-ratio dilutions. A synergistic interaction was previously reported between DB766 and posaconazole against intracellular L. donovani using parasites expressing a ␤-lactamase gene (7). The interaction between DB766 and posaconazole was examined using the high-content assay described above.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this regard, it was verified that butenafine was able to eliminate amastigote forms of L. amazonensis and L. braziliensis, species that cause the most serious forms of cutaneous leishmaniasis in Latin America, the anergic diffuse and mucocutaneous leishmaniasis. Antifungal drugs such as ketoconazole, voriconazole, fluconazole, itraconazole and other azoles already were related to possess effect against amastigote forms of L. mexicana, L. amazonensis, L. major and L. donovani [2,5,6,17,20]. Similarly, the effect of antifungal allylamines was evaluated in leishmaniasis, and different studies showed that terbinafine, naftifine, and SF 86-327 drugs were able to eliminate intracellular or axenic amastigotes [6,33].…”
Section: Discussionmentioning
confidence: 99%
“…Our efforts to explore the mechanism of antileishmanial action of the bis-AIAs led to the observation that DB766 is synergistic with posaconazole against Leishmania donovani in vitro 17 ; other investigators reported in vitro antileishmanial synergy between posaconazole and the squalene synthase inhibitor E5700. 18 A combination study with 1b and posaconazole was thus performed against intracellular L. amazonensis amastigotes.…”
mentioning
confidence: 99%